Narrative Skills and Social Class - Peterson, Carole (Canadian Journal of Education/Revue canadienne de l'éducation, 1994)
Narratives play an important role in education, for pragmatic and theoretical reasons. Nar- rative skills of four-year-old children are hypothetically important for later school success. This research investigated the relationship between specific narrative skills and social class in a culturally and racially homogeneous sample, focusing particularly on narratives of economically disadvantaged children from disorganized households. Both middle-class and economically disadvantaged children (but not economically disadvantaged children from disorganized households) often produced long and informative narratives. In contrast, children from disorganized households were most likely to produce extremely minimal narratives, and even their longer ones tended to be chronologically disorganized and poor- ly patterned in terms of overall structure. Since narrative is one building block teachers use pedagogically, such differences in the match between child skills and school demands at school entrance are cause for concern. Les récits jouent un rôle important en éducation et ce, pour des raisons pratiques et théo- riques. Les talents de narration des enfants de quatre ans sont hypothétiquement impor- tants pour la réussite ultérieure à l’école. Dans sa recherche, l’auteure s’est penchée sur la relation entre certains aptitudes narratives des enfants et leur classe sociale au sein d’un échantillon homogène du point de vue culturel et racial, en mettant l’accent sur les récits d’enfants défavorisés provenant de ménages désorganisés. Les enfants de classe moyenne comme les enfants défavorisés (mais non les enfants défavorisés provenant de ménages désorganisés) produisent des récits longs et détaillés. Les enfants de ménages désorga- nisés, quant à eux, sont plus susceptibles de produire des récits très courts, et même leurs récits plus longs ont tendance à manquer d’organisation chronologique et à être dans l’ensemble mal structurés. Comme les récits constituent l’un des outils pédagogiques des enseignants, de telles divergences entre les aptitudes des enfants et les exigences pédagogiques vis-à-vis des enfants qui entrent à l’école soulèvent des inquiétudes.